A Review of Classification of Nanomaterials with its Properties and Applications: Exploring the Advancements and Potential of Nanomaterials (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Nanotechnology is a known field of research since last century. Different major advances haveoccurred in the field of nanotechnology since the concept of nanotechnology was first introduced byNobel laureate Richard P. Feynman in his well-known 1959 lecture There's Sufficiently of Room at theBottom (Feynman, 1960). Using nanotechnology, researchers have been able to create new materials atthe nanoscale.Nanomaterials are essential building blocks in nanoscience nanotechnology. The fieldwith the earliest beginning most significant successes is the exploration of nanomaterialsnanostructures. The nanostructure science technology has grown rapidly in the last several years,encompassing an open range of disciplines. A wide range of novel functions materials might begenerated, as well as a new generation of products could be created.